The Salient Features of Medina Market in the Early Islam and its Relevance Today - Humaidi, Muchtim (El-Barka Journal of Islamic Economics and Business, 2020)
Islam is universal and final religion for all mankind both material and spiritual is situated in balance to ensure individual’s happiness in this life and here after. One facet of numerous aspects of one’s happiness is relates to human being is wealth that accumulated in permissible manner and to expend it in a way permitted by God. Apart from a universal messenger of God, Holy Prophet (PBUH) was a successful merchant in his own.  He guides all of business activity based on sharÄ«Ê¿ah pillars (al-QurÄn and al-Sunnah). As the result, this guide has brought a successful business not only among Muslim community but also produce great advantage to build a just order in the economic system for all generations. This paper is a qualitative research utilizing a literature and historical approach to portray the emerging market in early Islam of Medina as par-excellent model to be imitated and practiced in our modern day as in the case of mu’amalah market in Surabaya and Norwich. The results of the study states that the market based on simplicity, honesty, justice, freedom, responsibility, transparency, prohibiting riba and others. These principles are a key to solve many problems of contemporary business. Muslim community should realize the important of these principles in their daily life in order to highlight the principle of sharÄ«Ê¿ah. Although, this system was not famous among the economic system today, it will become a solution to develop Islamic market in Islamic community as well in a civil society.Islam adalah agama universal dan final untuk semua umat manusia, baik secara material maupun spiritual ditempatkan dalam keseimbangan untuk memastikan terwujudnya kebahagiaan hidup baik di dunia, maupun di akhirat nanti. Salah satu aspek dari banyak aspek kebahagiaan manusia adalah kekayaan yang terkumpul dengan cara yang diperbolehkan dan untuk dimanfaatkan dengan cara yang sudah diatur oleh Tuhan. Selain sebagai utusan universal Tuhan, Nabi SAW adalah juga termasuk sosok pedagang yang sukses. Dia membimbing dan menjalankan semua aktivitas bisnisnya berdasarkan tuntunan pilar syari'ah (al-QurÄn dan al-Sunnah). Alhasil pedoman ini telah membawa bisnis yang sukses, tidak hanya di kalangan komunitas Muslim tetapi juga menghasilkan manfaat lain dan maslahah yang lebih luas dalam membangun tatanan yang adil dalam sistem ekonomi untuk semua komunitas dan lintas generasi. Makalah ini adalah penelitian kualitatif dengan menggunakan pendekatan literatur dan sejarah untuk menggambarkan pasar yang berkembang pada awal Islam di Madinah sebagai model yang baik untuk ditiru dan dipraktikkan di zaman modern sebagaimana yang terjadi dalam pasar mu'amalah di Surabaya Indonesia dan Norwich London. Hasil penelitian menyatakan bahwa pasar didasarkan pada kesederhanaan, kejujuran, keadilan, kebebasan, tanggung jawab, transparansi, larangan riba dan lain-lain. Prinsip-prinsip ini adalah kunci untuk menyelesaikan banyak masalah dalam bisnis kontemporer. Umat Islam harus menyadari pentingnya prinsip-prinsip syariah yang universal ini, untuk tetap terjaga dan dijalankan dalam kehidupan sehari-hari. Meskipun sistem ini belum terkenal di antara sistem ekonomi saat ini, namun akan menjadi solusi untuk mengembangkan pasar syariah di masyarakat Islam maupun di masyarakat luas.